Determinants of the expansion of distance learning in undergraduate courses at private institutions in Brazil - Azevedo, Mario Luiz Neves de (2023)
The paper aims to analyze the accelerated growth of distance education (EaD – acronym in Portuguese), its relationship with the COVID-19 pandemic and the advancement of digital technologies in teacher training in a context of private-commercial domain and capitalism platform. Digital business platforms and private HEIs are driving the growth of distance learning, transforming it into a profitable market. These peculiar service companies act as intermediaries, connecting students, teachers, and educational institutions through their digital platforms. The analysis undertaken here considers data from the INEP Higher Education Census since the last decade of the 20th century, focusing, however, on more recent times, from the triggering of the COVID-19 pandemic which, in our understanding, served as a catalyst for the exorbitant expansion of EaD. The article seeks to establish the debate on equal access to education, digital inclusion, as well as reflecting on the privacy of the actors involved in the teaching-learning process and also on the conflict between public and private, especially in teacher training in Brazil.